SOLIDARITY DURING COVID-19 PANDEMIC ( A CASE STUDY ON THE SOCIAL ACTION OF YOGYAKARTA FOOD SOLIDARITY AND THE INTERFAITH NETWORK FOR COVID-19 RESPONSE) - Didid Haryadi; Devira Nur Malitasari (University of Muhammadiyah Malang, 2020)
Reality pandemic Covid-19 has a significant impact on the social, economic, political, and cultures around the world. Covid-19 which hit Indonesia has brought organic collective awareness from civilians through social movements. Initiatives from citizens to help one another are based on three things; the existence of a collective identity, a sense of injustice, and solidarity. This research focuses on two social movements initiated by ‘Solidaritas Pangan Jogja’ (SPJ) and ‘Jaringan Lintas Iman Tanggap Covid-19’ (JIC). The basic principles of mutual assistance, spontaneous collective awareness, and the same social needs form a pattern of solidarity and social movement in these two organizations. Therefore, this research focuses on the process of forming social awareness patterns that are manifested through collective behavior. This research uses a qualitative approach through case studies. Social solidarity and social movements are two concepts that are used as a basis for data analysis. There are two differences between the SPJ and JIC movement patterns. This research uses a qualitative approach through case studies. Social solidarity and social movements are two concepts that are used as a basis for data analysis. There are two differences between the SPJ and JIC movement patterns. The SPJ movement can be categorized as a conventional social movement with an orientation towards creating collective and cross-class social awareness. Whereas the JIC movement is a kind of new social movement which using the basics of the collectivity to understand norms and religious values. While the similarity of the two movements is always to prioritize the distribution of human values that are sustainable. The determining factor for the formation of a collective movement depends not only on the material resources available, but rather on the strength of ideas and cultural resources. That is about the articulation and collective construction of a new relationship (or redefinition) between the person as an individual and the person (as an ulama or cleric, citizen, and family). The SPJ movement carries the value of nativism while the JIC movement is a representation of the growth of new social movements that arise because of the spread of religious values in the social, cultural, economic, and political dimensions as citizens.Keywords: Pandemic Covid-19, Solidaritas Pangan Jogja (SPJ), Jaringan Lintas Iman Tanggap Covid-19 (JIC), Social Capital, Social Movement